2016
DOI: 10.15171/jrip.2017.08
|View full text |Cite
|
Sign up to set email alerts
|

Old habits die hard; does early urinary catheter removal affect kidney size, bacteriuria and UTI after renal transplantation?

Abstract: Introduction: Renal transplantation is the treatment of choice in chronic renal failure patients. Objectives: The purpose of this study was to evaluate the impact of urinary catheter removal time on transplanted kidney size and incidence of asymptomatic bacteriuria and urinary tract infections (UTIs). Patients and Methods: This retrospective cohort study evaluated the clinical outcomes of 109 consecutive live donor renal transplant recipients from December 2011 to July 2014. Routine ultrasound examinations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Foley d1 recipients (n=186) versus Foley >d1 recipients (n = 327) were significantly less likely to have pretransplant antibodies against human leukocyte antigens and have a ureteral stent placed at transplantation ( Table 2 ). 2 , 3 , 4 , 6 Urine leak occurred in 1.1% of Foley d1 and 1.2% of Foley >d1 recipients ( P > 0.99). The d1 group was significantly more likely to experience Foley reinsertion or intermittent catheterization after removal (11% vs 5%, P = 0.02) and less likely to have length of stay >4 days (47% vs 57%, P = 0.03).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Foley d1 recipients (n=186) versus Foley >d1 recipients (n = 327) were significantly less likely to have pretransplant antibodies against human leukocyte antigens and have a ureteral stent placed at transplantation ( Table 2 ). 2 , 3 , 4 , 6 Urine leak occurred in 1.1% of Foley d1 and 1.2% of Foley >d1 recipients ( P > 0.99). The d1 group was significantly more likely to experience Foley reinsertion or intermittent catheterization after removal (11% vs 5%, P = 0.02) and less likely to have length of stay >4 days (47% vs 57%, P = 0.03).…”
mentioning
confidence: 90%
“… 1 Bladder catheterization has remained constant. 2 , 3 , 4 , 5 , 6 Foley catheter use facilitates bladder identification by retrograde saline infusion into the bladder before anastomosis. After transplantation, the Foley catheter prevents tension on the new anastomosis by continuous drainage of urine and is typically maintained in place for 4-10 days to prevent urinary complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, early catheter removal may also be beneficial to pancreas transplant recipients. They are routinely inserted in renal transplant to allow for close monitoring of urine production, but multiple studies have shown that patients can safely tolerate catheter removal within 48 h of surgery [ 212 , 213 , 214 , 215 ]. Meta-analyses within other surgical specialities have demonstrated decreased incidence of urinary tract infections and retention with early removal [ 216 , 217 ].…”
Section: Postoperative Eras Componentsmentioning
confidence: 99%
“…1 Urinary tract infection (UTI) is the most common nosocomial infection in the post-transplantation period, ranging from 35% to 79% prevalence. 2,3 Sequelae range from no impairment to allograft function, through to allograft loss and death. 2 Risk factors for UTIs can be divided into recipient, donor, and procedure related factors.…”
Section: Introductionmentioning
confidence: 99%